Evolution of quality of life in patients with Korsakoff's syndrome in a long-term care facility. (December 2014) - Oudman, Erik; Wijnia, Jan W.; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Korsakoff's syndrome (KS) is a neuropsychiatric disorder characterized by severe amnesia. Quality of life (QoL) is becoming an increasingly used outcome measure in clinical practice but little is known about QoL in KS and how it may change over time. The purpose of this study was therefore to assess the QoL in patients with KS at baseline and with a 20-month follow-up. Methods: The current study is a longitudinal study on the QoL in patients with KS living in two long-term care facilities for KS patients in the Netherlands. QoL was scored with the proxy-based QUALIDEM scale with a 20-month follow-up. Results: Of the 72 KS patients included at baseline, 57 KS patients had a follow-up QoL score (79.2%). On the subscales "Feeling at home, " "Positive affect, " and "Care relationship" of the QUALIDEM, there was a better QoL in the follow-up, although effects were relatively small. Other subscales indicated a stable QoL over time. There were inter-relations between changes in subscales. Conclusions: The main finding of this study is that patients with KS on average do show a relatively stable moderate to good QoL despite the severity of the syndrome. On specific subscales, there is a small increase in QoL over time. Results do suggest that prolonged stay in a long-term care facility for KS patients does have a neutral to a positive effect on QoL in KS.